The social stratification of the German VET system - Protsch, Paula [Verfasser]; Solga, Heike [Verfasser] (My University, 2016)
"Germany is widely known for its vocational education and training (VET) system and its dual apprenticeship system in particular. What is often overlooked, however, is the vertical stratification within the German VET system. This is the focus of this study. Our analysis shows that the VET system, like the German school system, is highly stratified, resulting in large differences in labour market opportunities. We elaborate on three dimensions of vertical stratification: VET system vs. higher education, fully qualifying vs. prevocational VET programmes and segmentation of the fully qualifying VET programmes by educational attainment and career prospects. All three stratification dimensions are closely linked to school attainment and thereby to social origin." (Authors' abstract ; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 1.3.3.3 Mobilität; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; P 2.2 An- und Ungelernte; Berufsbildungssystem; Duales System; Vertikale Mobilität; Durchlässigkeit im Bildungssystem; Geringqualifizierter; Soziale Schichtung